2020
DOI: 10.25134/ijete.v1i1.2873
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Cooperative Learning Models Toward Pre-Service Elementary Teacher�s Understanding on Social Science Education Course: A Comparison for Cooperative Script, Articulation, and Guided Note Taking

Abstract: Our initial study in the course showed that there was a lack of students� understanding about social science. The purpose of this study was to investigated the effectiveness of using Cooperative Learning Model (Cooperative Script, Articulation, and Guided Note Taking) towards Pre-Service Elementary Teacher understanding on Social Science Course. This research was conducted in quasi-experimental research, with counterbalance research design. The subjects of this study were first year of undergraduate students o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
2
0
2
Order By: Relevance
“…the respondents' statements are positive regarding the fact that CT ensures the active participation of students in the learning and teaching process. The data of question (1) is in line with other researches where it was found that students during CT are more enthusiastic during the educational process, thus they are more active (Chatzidimou & Anagnostopoulou, 2011;Hermawati et al, 2020;Jakavonytė -Staškuvienė, 2021;Johnson et al, 2000;Nikolakaki et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…the respondents' statements are positive regarding the fact that CT ensures the active participation of students in the learning and teaching process. The data of question (1) is in line with other researches where it was found that students during CT are more enthusiastic during the educational process, thus they are more active (Chatzidimou & Anagnostopoulou, 2011;Hermawati et al, 2020;Jakavonytė -Staškuvienė, 2021;Johnson et al, 2000;Nikolakaki et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…In line with question (2) that a neutrality emerges in teachers' statements, research and studies have been identified where this neutrality and ambivalence are related to this neutrality and ambivalence. More specifically, on the one hand, research has found that in CT, students participate to a higher degree in discussions compared to their peers who do not work cooperatively since each student projects his/her individuality in the group which makes him/her unique and different (Chatzidimou & Anagnostopoulou, 2011;Gillies & Ashman, 1998;Gillis, 2006;Hermawati et al, 2020;Johnson & Johnson, 1994;Johnson et al, 2000;Nikolakaki et al, 2010). It has been observed that group members feel more comfortable expressing their opinions when working in small groups rather than in the whole classroom (Jakavonytė -Staškuvienė, 2021;Nikolakaki et al, 2010;Pimple, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membaca pemahaman sangat penting dalam kehidupan seiring dengan pertumbuhan pengetahuan dan teknologi informasi dan komunikasi yang semakin cepat (Budiman et al, 2018). Semua ini tidak dapat diperoleh oleh siswa begitu saja, tanpa perantara guru dan adanya kegiatan proses pembelajaran (Hermawati et al, 2020). Pada saat ini proses pembelajaran di sekolah menggunakan kurikulum 2013 yang mana setiap mata pelajaran disatukan menjadi tema.…”
Section: Pendahuluanunclassified
“…Hal ini berarti penerapan model CS ini dapat memberikan kontribusi untuk meningkatkan kemampuan pemahaman konsep siswa dari penerapan model Artikulasi. Hal ini sejalan dengan hasil penelitian yang dilakukan (Fatmawati, 2016;Hermawati et al, 2020;Rifa'i, 2015;Suwardi & dkk, 2016) mengindikasikan bahwa model pembelajaran CS berpengaruh signifikan terhadap pemahaman siswa dalam muatan pembelajaran IPS.…”
Section: Efektivitas Model Cs Dan Model Artikulasi Terhadap Pemahaman Konsep Siswaunclassified